Diabetes Self-Management Education (DSME) Intervention to Improve Self-Care Management of Diabetes Mellitus Patients - Annisa Wuri Kartika; Widyatuti Widyatuti; Etty Rekawati (Journal of Nursing Science Update (JNSU), 2021)
Self-care management is an important component in the management of Diabetes Mellitus Type 2 (DMT2). Knowledge, self-efficacy, and compliance in self-care are the main factors to improving quality of life and preventing complications. Diabetes Self-Management Education (DSME) in support groups was used in community nursing interventions to improve diabetes self-care management. This study used a one-group pre-post design with t-test analysis to determine the ability of self-management levels and blood sugar values of the group with diabetes before and after the intervention. The instrument used was the Diabetes Self Care Management Questionnaire (DSMQ). Diabetes Mellitus patients received DSME intervention for two months. The number of samplings in this study was 49 people with diabetes. The findings show that in intervention groups, self-care improves, and blood sugar levels fall. There were significant changes in the diabetics' group (n = 48) before and after the intervention on self-care and blood glucose levels (p = 0.000 and p = 0.011). We suggest that the DSME might be given to the diabetes group by nurses as one of the strategies for implementing health education in the public health care program (PERKESMAS).Â